Effect of Different Manganese Concentrations during in vitro Maturation of Bovine Oocytes on DNA Integrity of Cumulus Cells and Subsequent Embryo Development - Anchordoquy, Juan Patricio (2013)
Manganese (Mn) is a trace element present in forages and cereals, and its concentration depends on soil status. Manganese deficiency in cattle, goats and ewes not only impairs oestrous cycle but reduces calf birth weight. The achievement of the first oestrus is delayed, and more attempts are necessary to obtain a successful conception. This study was conducted to investigate the effect of the availability of supplemental Mn during IVM on DNA damage of cumulus cells and total glutathione (GSH) content in oocytes and cumulus cells. The effect of supplementary Mn during IVM on subsequent embryo development was also studied. The results reported here indicate (i) DNA damage in cumulus cells decreased with 0, 2, 5 and 6 ng/ml Mn supplementation during IVM (p < 0.05). (ii) Intracellular GSHGSSG content increased (p < 0.01) with different Mn concentrations in oocytes and cumulus cells. Also, cumulus cell number per cumulus oocyte-complexes (COC) did not differ either before or after IVM. (iii) Addition of Mn to maturation medium resulted in similar cleavage rates (p > 0.05) at 0, 2, 5 and 6 ng/ml Mn. However, subsequent embryo development to blastocyst stage was significantly higher (p < 0.01) in oocytes matured with 5 and 6 ng/ml Mn. (iv) There was also an increase (p < 0.05) in mean cell number per blastocyst obtained from oocytes matured with 5 and 6 ng/ml respect to zero Mn (IVM alone) and 2 ng/ml Mn. This study provides evidence that optimal embryo development to the blastocyst stage was partially dependent on the presence of Mn during IVM. Moreover, the availability of Mn during oocyte maturation ensures ‘normal’ intracellular GSH content in COCs and protects DNA integrity of cumulus cells.